Efficacy of repetitive transcranial magnetic stimulation (rTMS) for reducing consumption in patients with alcohol use disorders (ALCOSTIM): study protocol for a randomized controlled trial - Benjamin Petit; Agnès Soudry-Faure; Ludovic Jeanjean; Jack Foucher; Laurence Lalanne; Maud Carpentier; Lysiane Jonval; Coralie Allard; Mathilde Ravier; Amine Ben Mohamed; Vincent Meille; Benoit Trojak (Trials, 2022)
Abstract Background The number of people with an alcohol use disorder (AUD) was recently estimated to be 63.5 million worldwide. The global burden of disease and injury attributable to alcohol is considerable: about 3 million deaths, namely one in 20, were caused by alcohol in 2015. At the same time, AUD remains seriously undertreated. In this context, alternative or adjunctive therapies such as brain stimulation could play an important role. The early results of studies using repetitive transcranial magnetic stimulation (rTMS) suggest that stimulations delivered to the dorsolateral prefrontal cortex significantly reduce cravings and improve decision-making processes in various addictive disorders. We therefore hypothesize that rTMS could lead to a decrease in alcohol consumption in patients with AUD. Methods/design We report the protocol of a randomized, double-blind, placebo-controlled, parallel-group trial to evaluate the efficacy of rTMS on alcohol reduction in individuals diagnosed with AUD. The study will be conducted in 2 centers in France. Altogether, 144 subjects older than 18 years and diagnosed with AUD will be randomized to receive 5 consecutive twice-daily sessions of either active or sham rTMS (10 Hz over the right DLPFC, 2000 pulses per day). The main outcomes of the study will be changes in alcohol consumption within the 4 weeks after the rTMS sessions. Secondary outcome measures will include changes in alcohol consumption within the 24 weeks, alcohol cravings, clinical and biological improvements, effects on mood and quality of life, and cognitive and safety assessments, and, for smokers, an assessment of the effects of rTMS on tobacco consumption. Discussion Several studies have observed a beneficial effect of rTMS on substance use disorders by reducing craving, impulsivity, and risk-taking behavior and suggest that rTMS may be a promising treatment in addiction. However, to date, no studies have included sufficiently large samples and sufficient follow-up to confirm this hypothesis. The results from this large randomized controlled trial will give a better overview of the therapeutic potential of rTMS in AUD. Trial registration ClinicalTrials.gov NCT04773691. Registered on 26 February 2021 https://clinicaltrials.gov/ct2/show/NCT04773691?term=trojak&draw=2&rank=5 .